Educação integral no campo : um estudo de caso no povoado Carrilho em Itabaiana-SE - Menezes, Aline da Conceição Miguel de (2015)
This dissertation objectified to know the meaning of the Programa Mais Educação/Educação Integral for coordinators, professors and monitors of school of the field, situated in the Town Carrilho in the Itabaiana City, state of Sergipe. For in such a way, in we propose them to describe and to analyse the process of implementation of the Programa Mais Educação/Educação Integral in the town; to reflect on the purpose of the Programa Mais Educação in the context peasant; and to identify that meanings the subject ones attribute to the Programa Mais Educação . The investigation is anchored in the presuppositions of the boarding of qualitative research in education. The used methodology is the fenomenologia-hermeneutics and the type of research is case study. The instruments used in the collection of data were daily of official field, documents, and half-structured interviews. We conclude from this research that the meanings attributed to the Programa Mais Educação are placed in the scope of protecting, keeping and to strengthen the studies for children, adolescents and young, evidencing a dissonance with the aims of the referred to Program. The concept of Integral Education not always is understood by the subject ones as education that exceeds the dimension weather of permanence in school for a human training that, beyond guarantee the rights of the children and adolescents, advances in the direction of instrumentalizar them for the understanding of the field as space of production of the life and development. The importance and the complexity of the Integral Education for the development of the interviewed field did not receive no mention on the part from the subject ones, demonstrating we who this not yet effective relation as social practice in the searched context. One expects with the results of this research to contribute to extend the debate on the implementation of the Integral Education in the Field.